(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The English article system, comprising the definite article the and the indefinite articles a/an, plays a crucial role in expressing semantic nuances such as definiteness, specificity, familiarity, and genericity. This paper explores the semantic functions of these articles in contemporary English, highlighting how contextual and cognitive factors influence article usage. The study draws on current linguistic theories and examples from corpora to demonstrate the complexity and adaptability of article semantics in modern usage